A Comparative Approach for the Preparation and Physicochemical Characterization of Lecithin Liposomes Using Chloroform and Non‐Halogenated Solvents. Issue 4 (12th May 2015) - Naeem, Sumaira; Kiew, Lik Voon; Chung, Lip Yong; Fui, Kiew Siaw; Misran, Misni Bin
Abstract: Organic solvents used in various pharmaceutical preparations may be associated with chronic health effects, with special emphasis on halogenated solvents. Liposomes, lipid bilayer membrane carriers, have potential applications in targeted drug delivery systems. The non‐halogenated solvents, acetonitrile and ethanol, were used in comparison to commonly used chloroform. The effect of solvents and dispersion medium was demonstrated using physicochemical properties, stability studies and hemolytic activity. Increased sonication time showed decreased particle size in phosphate buffer saline and water medium. Vesicles prepared from all solvents exhibited better stability in phosphate saline buffer than water when evaluated by particle size and zeta potentials. Liposomes showed a positive zeta potential in buffer solution whereas liposomes in water showed negative zeta potential. In vitro hemolytic activity of liposomes was done with fresh human red blood cells. Results in buffer solution were in the range of 1–4 % which further proved this medium superior to pure water. The findings of this study are helpful in suggesting the formulation of thin films by less hazardous solvents in terms of the environmental integrity and human health.